Peran Pemerintah Kota Surabaya dalam Menanggulangi Bencana Banjir di Kecamatan Pakal Kota Surabaya - Syahtoni, Mohamad Geoveza Putra; Pangestu, Aryan Adi; Bagaskara, Prayoga; Putratama, Bonifasius Deva; Reviandani, Oktarizka (VISA: Journal of Vision and Ideas, 2024)
Surabaya City is one of the cities that has the potential for flooding, especially in the Pakal District area, which is a flood-prone area almost every year. At least in the Pakal District area itself, there are approximately seven flood inundation points that occurred some time ago with a fairly varied inundation height ranging from 15 cm to 1 meter. This study uses a qualitative descriptive approach. Primary data were obtained from interviews conducted by researchers with employees of the Surabaya City BPBD and Surabaya City DSDABM, while secondary data were obtained from written sources such as documents, reports, and other archives. The data collection technique for this study used observation and interviews, then analyzed using data analysis techniques. Based on the role theory according to Siagian, including the government as a stabilizer, the government as an innovator, the government as a modernizer, the government as a pioneer, and the government as the implementer itself, the results found that the Surabaya City government, through the DSDABM of Surabaya City and the BPBD of Surabaya City, were quite successful in overcoming the flood disaster in Pakal District, Surabaya City, with various policy efforts. Although it was considered successful, there are several suggestions that can be used by the DSDABM of Surabaya City and the BPBD of Surabaya City in increasing its capabilities in overcoming this flood problem by strengthening communication synergy between OPDs, service innovation, and community empowerment.